Electroconvulsive therapy in children and adolescents - Ghaziuddin, Neera; Walter, Garry (Oxford University Press, 2014)
This pioneering book is the first book of its kind and offers guidance about the use of ECT in youth with up-to-date and concise information. The editors, Neera Ghaziuddin MD, MRCPsych (University of Michigan, Ann Arbor, USA), and Garry Walter, MD, PhD (University of Sydney, Australia), have spearheaded the re-introduction of ECT as a safe and an effective treatment option for a subgroup of children and adolescents with severe psychiatric disorders. This book offers a review of the existing literature, firsthand experience of the authors who are regarded as experts in their respective field, a.